D-STEM Equity Model: Diversifying the STEM Education to Career Pathway - Adrienne Coleman (Athens Institute for Education and Research, 2020)
According to the National Science Foundation, "the U.S. STEM workforce must be considered in the context of an expanding and vibrant global scientific and technological enterprise" (2014). "The National Academy of Sciences further suggests that, without the participation of individuals of all races and genders, the increasing demand for workers in STEM fields will not be met, potentially compromising the position of the United States as a global leader" (2014). The stark reality is that there are a disproportionate number of Black and Latinx students who lack the access and exposure to become STEM-literate. In order for the U.S. to remain a global STEM leader, an intricate look at STEM inequity on a national scale must occur and diversifying the STEM education to career pathway must be a priority. The Illinois Mathematics and Science Academy sought to gain a better understanding of how to diversify this STEM education to career pathway. Thus, a study was conducted on the motivation of Black and Latinx students to engage in STEM as well as two Diversifying STEM Think Tanks held, to understand and address the racial STEM divide. From the perspectives of 415 STEM Stakeholders (students, parents, professionals, and educators) the D-STEM Equity Model to diversify the STEM Education to Career Pathway with national implications and global scalability was developed. This model suggests "diversifying STEM policies" need to be developed that mandate funding for racially-based collaborative STEM initiatives to be implemented, that work towards achieving equity by addressing the identified problems collectively and integrating factors of Black and Latinx student STEM motivation into STEM programming as well as encourage culturally responsive STEM educator training.